Oxidative DNA Damage and Repair: Mechanisms, Mutations, and Relation to Diseases - Marina Roginskaya; Yuriy Razskazovskiy (Antioxidants, 2023)
Oxidative DNA damage (ODD) by reactive oxygen species (ROS) or reactive nitrogen species (RNS) is an inevitable tradeoff for using oxidation processes by living cells as a source of energy [...]